Early venous return in hepatic angiomyolipoma due to an intratumoral structure resembling an arteriovenous fistula. Issue 6 (20th June 2013) - Iwao, Yasuhito; Ojima, Hidenori; Onaya, Hiroaki; Sakamoto, Yoshihiro; Kishi, Yoji; Nara, Satoshi; Esaki, Minoru; Mizuguchi, Yasunori; Ushigome, Masahiko; Asahina, Daisuke; Hiraoka, Nobuyoshi; Shimada, Kazuaki; et al.
<x xml:space="preserve">Abstract</x> Early venous return (EVR) is an important radiological feature of hepatic angiomyolipoma (HAML) that can aid in differential diagnosis, but the pathogenic mechanisms of EVR have yet to be elucidated. We present the first HAML case for which a probable mechanism for EVR is described. The patient was a 46‐year‐old woman, who had a growing 6‐cm tumor with EVR in segment 3 of the liver as revealed by dynamic contrast‐enhanced computed tomography. Left hepatic lobectomy was performed to prevent tumor rupture. Histopathological and immunohistochemical analyses of the excised tumor indicated HAML. Successive microsections of the tumor were stained with hematoxylin–eosin and Victoria blue to visualize the vascular structure within and around the tumor. These analyses led to three major findings. First, many well‐defined thick‐walled vessels, such as arteries, were found entering the tumor. Second, many thick‐walled vessels within the tumor were connected directly to thin‐walled vessels, resembling arteriovenous fistulae. Finally, thin‐walled intratumoral vessels were connected directly to the hepatic vein. These histological findings suggested that the rich arterial flow into the tumor was being rapidly drained into the hepatic vein through intratumoral arteriovenous connections. We also detected these same anomalous circulatory pathways in tissue sections from three of four additional HAML cases with EVR. Aberrant arteriovenous fistulae within the tumor may account for many cases of EVR in HAML patients.